2002
DOI: 10.1080/00221300209602105
|View full text |Cite
|
Sign up to set email alerts
|

Two Tests of the Stuck-in-Time Hypothesis

Abstract: The authors report 2 experiments that test the stuck-in-time hypothesis, which argues that animals cannot time-date events and thus do not remember when events occurred and do not anticipate future events. In Experiment 1, rats in the experimental condition could earn a large reward by reentering the 1st arm that they visited on a radial maze. They did not learn to reenter this arm early and did no better than did a control group that was not given a large reward for reentering the first arm. In Experiment 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…W. A. Roberts and S. Roberts (2002) assessed the ability of rats to remember the order in which they entered arms on a radial maze. The rats were unable to discriminate the first arm they encountered from the other arms.…”
Section: Discussionmentioning
confidence: 99%
“…W. A. Roberts and S. Roberts (2002) assessed the ability of rats to remember the order in which they entered arms on a radial maze. The rats were unable to discriminate the first arm they encountered from the other arms.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches provide independent evidence for episodic memory in rats (Eacott & Easton, 2012, this issue; Eacott, Easton, & Zinkivskay, 2005; Zhou, Hohmann, & Crystal, in press) but are beyond the scope of this review. Efforts to document memory for a specific earlier event in rats have been complicated by some initial attempts that did not produce robust memory (Bird, Roberts, Abroms, Kit, & Crupi, 2003; Roberts & Roberts, 2002). Subsequent studies suggested that rats remember what-where-when (Babb & Crystal, 2005, 2006a, 2006b; Eacott, et al, 2005; Eacott & Norman, 2004; Kart-Teke, De Souza Silva, Huston, & Dere, 2006; Naqshbandi, Feeney, McKenzie, & Roberts, 2007).…”
Section: Rats Remember When An Earlier Episode Occurredmentioning
confidence: 99%
“…One successful approach has been to test for specific aspects of episodic memory in nonhumans, rather than attempting to capture all the properties of episodic memory with a single paradigm (e.g. Clayton et al, 2001; Clayton and Russell, 2009; Dere et al, 2006; Fortin et al, 2002; Hampton and Schwartz, 2004; Roberts and Roberts, 2002). The study of memory for the order of unique events appears to capture some aspects of episodic memory (Fortin et al, 2002; Kesner et al 2002).…”
Section: Introductionmentioning
confidence: 99%